The duties of the almoner (memorandum) - Mudd, Edith E.
1901-10-25 1901 1900s 5 pages of the Medical School, which I am always endeavouring to study. I must apologise it I give offence in citing one of these ways. I take it the Sunday Fund would not consider an Inquiry Officer should blink at the fact that rich people's servants should use their employer's names to attend for things they ought to be ashamed to ask medical charity for. It is an abuse of the worst sort. These Servants can well afford to pay for their treatment and often unblushingly come with a letter of recommendation from their mistress. I do not hesitate to explain to them what is meant by Hospital Charity, and some not return. If they did and I brought the matter to the Board, I should be told that "Lady So-and-So is a Subscriber, the matter had better be left." I do not doubt for a moment these servants speak of the casual treatment they receive but surely, if passed with no remark, it would scarcely be what the Hospital Sunday Fund meant as the duty of an Inquiry Officer. Passing to Class II.- Negligence of Patients in carrying out the Doctors' treatment etc. - as illustration of what I mean the following cases might be instanced. I recently found a mother emptying away two-thirds of a bottle of Maltine, because it was her day for the Hospital, and she had forgotten to give it to the child, and wanted to get the bottle refilled. Another, with whom one felt more sympathy, was impartially divided the cod-liver oil between four children, three of whom were not Out-Patients, and one of my visitors repeatedly found a child of thirteen up, and running about in her mother's sight, when the surgeon had ordered that she should absolutely be lying on her back. She finally became so bad from sheer negligence, as to have to come into the Hospital. I could quote very many cases on this point, but only wish to draw your attention to the fact that prevention of this form of abuse can only be met by visits to the home made by, or at the instigation of, the Almoner. 378/IMSW/A/1/4/3a